2011
DOI: 10.1007/s00024-011-0271-9
|View full text |Cite
|
Sign up to set email alerts
|

The Micromechanics of Westerley Granite at Large Compressive Loads

Abstract: Abstract-The micromechanical damage mechanics formulated by ASHBY and SAMMIS (Pure Appl Geophys 133(3) 1990) has been shown to give an adequate description of the triaxial failure surface for a wide variety of rocks at low confining pressure. However, it does not produce the large negative curvature in the failure surface observed in Westerly granite at high confining pressure. We show that this discrepancy between theory and data is not caused by the two most basic simplifying assumptions in the damage mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
43
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(44 citation statements)
references
References 28 publications
1
43
0
Order By: Relevance
“…[2,12,13] calculate the shear (s) and normal (r) stresses on each penny crack from the remote compressive stress field.…”
Section: Evaluation Of the Stress Intensitymentioning
confidence: 99%
See 1 more Smart Citation
“…[2,12,13] calculate the shear (s) and normal (r) stresses on each penny crack from the remote compressive stress field.…”
Section: Evaluation Of the Stress Intensitymentioning
confidence: 99%
“…It was later shown by [13] that the inclusion of size distribution of cracks and allowance for multiple crack orientations did not significantly effect the failure strength predicted by the model. We thus retain the single-crack single-orientation assumption of [2,12].…”
Section: Introductionmentioning
confidence: 99%
“…1); r 3 is the least compressive stress and the stresses are considered positive in tension. Bhat et al (2011) showed that the inclusion of size distribution of cracks and allowance for multiple crack orientations do not significantly affect the failure strength predicted by the model used here. Therefore, we retain the single-crack size and single-orientation assumption.…”
Section: Wing Crack Model Ashby and Sammis (1990)mentioning
confidence: 83%
“…The Ashby/Sammis damage mechanics upon which all this work is based is sometimes criticized because it assumes that all the active flaws have the same size and orientation. In Bhat et al [15] we focused on Westerly Granite (one of the most studied rocks) and explored the effects of allowing a range of flaw sizes and orientations consistent with petrologic studies. We found that relaxing the assumption of a single flaw size and orientation had little or no effect on the predicted failure surface.…”
Section: Resultsmentioning
confidence: 99%